2006
DOI: 10.1590/s1516-35982006000300028
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação nutricional do milho com maior teor de óleo, nas formas de grãos secos e silagens, para suínos nas fases de crescimento e terminação

Abstract: RESUMO -Dois experimentos foram conduzidos para determinação do valor nutritivo de rações contendo milho com maior teor de óleo, nas formas de grão seco (MSe), silagem de grãos úmidos (SGUM) e silagem de milho seco reidratado (SH) e avaliação do desempenho de suínos em crescimento e terminação alimentados com essas rações. No ensaio de digestibilidade foram utilizados 12 suínos mestiços, machos castrados, alojados em gaiolas e distribuídos em um delineamento experimental de parcelas subdivididas. Os valores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
3
9
0
3
Order By: Relevance
“…Corn density is influenced by genetic differences among cultivars, as well as other factors, according to Gutiérrez-Alamo et al (2008). Silva (2006) 3 ) density as determined in a gravity table, and concluded that higher density corn has higher energy value due to its higher starch content. Average crude protein values ranged from 7.2 to 9.1%, with an average 8.1%, similarly to those reported by Rostagno (2005) and Rostagno (2011), of 8.6 and 7.9%, respectively, but higher than those obtained by Agostini et al (2004), who obtained 7.3%, which is close to the minimum value obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Corn density is influenced by genetic differences among cultivars, as well as other factors, according to Gutiérrez-Alamo et al (2008). Silva (2006) 3 ) density as determined in a gravity table, and concluded that higher density corn has higher energy value due to its higher starch content. Average crude protein values ranged from 7.2 to 9.1%, with an average 8.1%, similarly to those reported by Rostagno (2005) and Rostagno (2011), of 8.6 and 7.9%, respectively, but higher than those obtained by Agostini et al (2004), who obtained 7.3%, which is close to the minimum value obtained in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, in feed milling, hard corn requires more energy for grinding and impairs particle-size uniformity. Moreover, higher concentrations of digestive enzymes are required to allow animals to properly digest these grains due to their vitreous characteristics (Silva et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…A ensilagem de grãos úmidos de milho é uma alternativa no armazenamento de grãos na propriedade rural, esta técnica diminui os custos por quilograma de animal produzido em relação ao milho seco (SILVA et al, 2006). Tradicionalmente, as silagens de grãos de milho são produzidas a partir de variedades pertencentes à espécie Zea mays L. Entretanto, grãos de milho doce pertencentes ao grupo saccharata, podem ser uma boa opção na produção de silagens de grãos úmidos, visto que, por apresentarem presença de alelos mutantes que bloqueiam a conversão de açúcar em amido, dão ao grão a caraterística de possuir um teor maior de açucares solúveis (ZÁRATE & VIEIRA, 2003), que podem favorecer as caraterísticas fermentativas em relação aos grãos de milho convencionais.…”
Section: Introductionunclassified